Data table of animal bones found in Vatnsvik, lake Þingvallavatn, Iceland [Structured Data from Open Context] - Albína H Pálsdóttir (Zenodo, 2023)
This deposit archives structured-data files associated with the Data table of animal bones found in Vatnsvik, lake Þingvallavatn, Iceland Data Table resource published by Open Context . In general, Open Context is a dynamic and frequently updated database that integrates research data from a growing number of sources. However, Open Context also stores some static and unchanging, externally stored "Data Table" files. Unless otherwise indicated, the content of Data Table files (such as the resource deposited here) will not change even after updates to the Open Context database. Deposition File Overview This archival deposit includes two files, in two formats: CSV : The 144-data-table-of-animal-bones-found-in-vatnsvik-lake-thing.csv contains the tabular data content for this resource in a CSV format. JSON : The 144-data-table-of-animal-bones-found-in-vatnsvik-lake-thing.json provides additional metadata about the tabular data content for this resource in a JSON-LD format. Open Context is an open-source Python application built with the Django framework (see source code and Docker deployment code ). To manage a wide variety of archaeological and related data, Open Context organizes information using a very abstract, graph-based schema. Open Context implements this schema using a Postgres relational database and the Django "Object Relational Model" (ORM). Because Open Context internally maintains data using a very abstract schema, data dumps directly from this schema would be difficult to understand and use. Therefore, Open Context makes select datasets (like this) available in more easily understood tabular expressions. A considerable amount of application logic in Open Context generated the more expressive tabular representation of data. This tabular data output from Open Context is meant to be considered as a static and unchanging "snapshot" of data selected for output at a specific time. Terms of Use, Intellectual Property, and Ethics Open Context publishes ...